Dual spindle formation in zygotes keeps parental genomes apart in early mammalian embryos - Reichmann Judith; Nijmeijer Bianca; Hossain M. Julius; Eguren Manuel; Schneider Isabell; Politi Antonio Z.; Roberti Maria J.; Hufnagel Lars; Hiiragi Takashi; Ellenberg Jan (University of Dundee, 2018)
At the beginning of mammalian life the genetic material from each parent meets when the fertilized egg divides. It was previously thought that a single microtubule spindle is responsible to spatially combine the two genomes and then segregate them to create the two-cell embryo. Utilizing light-sheet microscopy, we showed that two bipolar spindles form in the zygote, which independently congress the maternal and paternal genomes. These two spindles aligned their poles prior to anaphase but kept the parental genomes apart during the first cleavage. This spindle assembly mechanism provides a potential rationale for erroneous divisions into more than two blastomeric nuclei observed in mammalian zygotes and reveals the mechanism behind the observation that parental genomes occupy separate nuclear compartments in the two-cell embryo
Keywords: Embryology; mammalian embryo; zygote; spindle formation; light sheet microscopy